2019
DOI: 10.1186/s12914-019-0187-5
|View full text |Cite
|
Sign up to set email alerts
|

Experiences of gender-based violence among female sex workers, men who have sex with men, and transgender women in Latin America and the Caribbean: a qualitative study to inform HIV programming

Abstract: Background Female sex workers, MSM, and transgender women—collectively referred to as key populations (KPs)—are disproportionately affected by gender-based violence (GBV) and HIV, yet little is known about the violence they face, its gender-based origins, and responses to GBV. The purpose of this study was to understand the nature and consequences of GBV experienced, to inform HIV policies and programming and to help protect KPs’ human rights. Methods Using a participat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
48
1
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 66 publications
(57 citation statements)
references
References 41 publications
2
48
1
1
Order By: Relevance
“…The findings of the present study also showed that IPV was significantly associated with the alcohol misuse and dependence symptom outcomes. High-risk women generally experience high levels of IPV [ 29 ]. Acts of IPV remain unreported due to the criminalization of sex work in many parts of SSA [ 30 ]; disclosure rates are therefore low [ 31 ] and this undermines their ability to interact with society including community rehabilitation facilities where they could seek help.…”
Section: Discussionmentioning
confidence: 99%
“…The findings of the present study also showed that IPV was significantly associated with the alcohol misuse and dependence symptom outcomes. High-risk women generally experience high levels of IPV [ 29 ]. Acts of IPV remain unreported due to the criminalization of sex work in many parts of SSA [ 30 ]; disclosure rates are therefore low [ 31 ] and this undermines their ability to interact with society including community rehabilitation facilities where they could seek help.…”
Section: Discussionmentioning
confidence: 99%
“…Ramaiah S 2006 and Weitzer R 2009 pointed out that prostituted women access to welfare, health care services, and the right to have healthy reproduction is compromised [ 37 , 38 ]. In other studies, women have pointed out that there is no proper help and support for women involved in prostitution [ 3 , 15 , 55 , 56 ]. In the study of Asadi-Aliabadi M et al., 2018 in Iran, the results showed that prostitutes are less likely to receive health services, and they are less inclined to perform medical tests and receive health care due to the restrictions and pressures on them [ 57 ].…”
Section: Discussionmentioning
confidence: 99%
“…Health problems such as fatigue, viral diseases, backache, depression, headaches, etc., are also very prominent in prostituted women, and they may even be killed [ 13 , 14 ]. Evans E et al., 2019 studied prostitutes in El Salvador and highlighted problems like emotional and economic violence, lack of access to legal, health social services, and loss of income, job, housing, and educational opportunities [ 15 ]. Duff P et al., 2017 showed in a study in Uganda that prostitutes had several health needs in pregnancy and HIV fields in particular and Unplanned pregnancy was one of the main issues [ 16 ].…”
Section: Introductionmentioning
confidence: 99%
“…Women who are abused may not ask their partner to use a condom, nor have the efficacy to say no to sex if their abusive partner does not want to use protection, which will put abused women at a higher risk for HIV. Additionally, women who are transgender and are living with HIV are disproportionately impacted by intimate partner violence [24], stay at home COVID-19 orders could exacerbate their wellbeing.…”
Section: Health Systems and Services Inequitiesmentioning
confidence: 99%